Incidence, clinical relevance and therapeutic options for outflow graft stenosis in patients with left ventricular assist devices. (1st September 2021) - Dimitrov, Kamen; Kaider, Alexandra; Angleitner, Philipp; Schlöglhofer, Thomas; Gross, Christoph; Beitzke, Dietrich; Granegger, Marcus; Riebandt, Julia; Wiedemann, Dominik; Sandner, Sigrid; Schaefer, Anne-Kristin; Schima, Heinrich; et al.
Abstract:  : OBJECTIVES: We reviewed our institutional experience with outflow graft stenosis (OGS) in 3 contemporary left ventricular assist devices (LVAD). METHODS: Data from 347 consecutive adult recipients of LVAD [Medtronic HVAD ( n  = 184, 53.0%), Abbott HeartMate II ( n  = 62, 17.9%) and Abbott HeartMate 3 ( n  = 101, 29.1%)] implanted between March 2006 and October 2019 were analysed retrospectively. Primary study end points were the incidence of OGS necessitating treatment and survival on LVAD support. RESULTS: During the study period, 17 patients (4.9%) developed OGS requiring treatment with a probability of 0.6% at 1 year, 1.9% at 2 years, 3.8% at 3 years, 4.7% at 4 years and 5.9% at 5 years of LVAD support. Notably, in 13.8% of patients, a compression-related narrowing of the outflow graft with a probability of 1.5% at 6 months, 1.8% 1 year, 6.0% at 2 years, 12.3% at 3 years, 15.4% at 4 years and 16.6% at 5 years of LVAD support with no difference between devices ( P  = 0.26) was observed. There was a trend towards increased risk of mortality with OGS (hazard ratio 2.21, 95% confidence interval 0.87–5.51; P  = 0.09). OGS preferentially occurred in segments of the outflow graft covered by a protective coating. CONCLUSIONS: OGS is a rare but potentially lethal complication during LVAD support. Modifications of pump design and implant techniques may be needed because OGS preferentially occurs within covered portions of the outflow graft. Systematic screening may be warranted. Abstract : The durability of contemporary implantable left ventricular assist devices (LVAD) enables their use for long-term support.